Answer:
-1
Step-by-step explanation:
Move all terms containing x
to the left side of the equation.
Tap for fewer steps...
Subtract 4x from both sides of the equation.
2
x−10−4x= −8 y=4x−8
Subtract 4
x from 2
x
−
2
x−
10=
−
8
y
=
4
x
−
8
Move all terms not containing x to the right side of the equation.
Tap for more steps...
−
2
x
=
2
y
=
4
x
−
8
Divide each term by −
2 and simplify.
Tap for fewer steps...
Divide each term in −
2
x=
2 by −
2
.
−
2
x
−
2
=
2
−
2
y
=
4
x
−
8
Simplify the left side of the equation by cancelling the common factors.
Tap for fewer steps...
Reduce the expression by cancelling the common factors.
Tap for more steps...
−
(
−
1
⋅
x
)
=
2
2
y
=
4
x
−
8
Rewrite
−
1
⋅
x as - x
.
x
=
2
−
2
y
=
4
x
−
8
Divide 2 by −
2
.
x
=
−
1
y
=
4
x
−
8
Replace all occurrences of x with the solution found by solving the last equation for x
. In this case, the value substituted is −
1
.
x=
−
1
y
=
4
(
−
1
)
−
8
Simplify 4
(
−
1
)
−
8
.
Tap for fewer steps...
Multiply 4 by −
1
.
x
=
−
1
y
=
−
4
−
8
Subtract 8 from -
4
.
x
=
−
1
y
=
−
12
The solution to the system of equations can be represented as a point.
(
−
1
,
−
12
)
The result can be shown in multiple forms.
Point Form: (
−
1
,
−
12
)
Equation Form: x =−
1 ,y =
−
12